2017
DOI: 10.1007/s00115-017-0325-z
|View full text |Cite
|
Sign up to set email alerts
|

Umsetzung der S3-Leitlinie „Demenzen“ im klinischen Alltag: Wunsch oder Wirklichkeit?

Abstract: The German S3 guidelines on dementia were satisfactorily implemented in outpatient clinical practice; however, deficits existed in the frequency of the pharmaceutical treatment of patients with indications for therapy, the prescription of non-recommended drugs and the relatively common use of permanent neuroleptic medications. Interestingly, the motivation for implementation of the guidelines was not primarily influenced by the physicians' personal convictions but mainly stimulated by the expectations of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…International studies have already shown that the vast majority of patients does not receive guideline-based diagnoses (Nielsen et al, 2011;Phung et al, 2009). This contrasts with the results of a survey study among specialized outpatient physicians, in which 93% of all participants reported regular use of neuroimaging techniques and 27% reported the use of laboratory diagnostics for diagnosing dementia (Lohmann et al, 2017). However, the significance of these results is very limited, as only 8% of the originally contacted specialists participated in the survey, which might point at a substantial response bias.…”
Section: F I G U R E 2 Proportions Of Dementia Subtypes In Prevalent ...mentioning
confidence: 65%
See 1 more Smart Citation
“…International studies have already shown that the vast majority of patients does not receive guideline-based diagnoses (Nielsen et al, 2011;Phung et al, 2009). This contrasts with the results of a survey study among specialized outpatient physicians, in which 93% of all participants reported regular use of neuroimaging techniques and 27% reported the use of laboratory diagnostics for diagnosing dementia (Lohmann et al, 2017). However, the significance of these results is very limited, as only 8% of the originally contacted specialists participated in the survey, which might point at a substantial response bias.…”
Section: F I G U R E 2 Proportions Of Dementia Subtypes In Prevalent ...mentioning
confidence: 65%
“…Indeed, depending on the setting and methodology, AD proportions comparable to ours or even significantly lower have also been reported. For example, the AD proportion in the German outpatient specialist sector was estimated to be 25%–40% in a survey study (Lohmann et al., 2017 ). Even lower proportions of around 10% were previously found in health claims data (Albrecht et al., 2018 , 2019 ; Kaduszkiewicz et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%